Why Windows software? - Juran, Michael J. (Journal of Housing & Community Development)
The writer discusses the difficulties that local housing agency staff members encounter in using housing software, which seldom presents data and procedures in the order that they are familiar with, and considers the advantages of using graphical operating systems like Microsoft Windows. These advantages are outlined as including a reduction of the learning curve for most users, the easy availability of data, and an opening of a wealth of local resources to a housing agency for training, support, and additional software.